Multimodal X‐ray imaging of grain‐level properties and performance in a polycrystalline solar cell. (14th May 2019) - Ulvestad, A.; Hruszkewycz, S. O.; Holt, M. V.; Hill, M. O.; Calvo-Almazán, I.; Maddali, S.; Huang, X.; Yan, H.; Nazaretski, E.; Chu, Y. S.; Lauhon, L. J.; Rodkey, N.; et al.
Abstract : A multimodal in situ nanofocused X‐ray microscopy approach is demonstrated and applied to a working polycrystalline thin film solar cell that revealed chemical, structural and electronic heterogeneity from a single measurement. Abstract : The factors limiting the performance of alternative polycrystalline solar cells as compared with their single‐crystal counterparts are not fully understood, but are thought to originate from structural and chemical heterogeneities at various length scales. Here, it is demonstrated that multimodal focused nanobeam X‐ray microscopy can be used to reveal multiple aspects of the problem in a single measurement by mapping chemical makeup, lattice structure and charge collection efficiency simultaneously in a working solar cell. This approach was applied to micrometre‐sized individual grains in a Cu(In, Ga)Se2 polycrystalline film packaged in a working device. It was found that, near grain boundaries, collection efficiency is increased, and that in these regions the lattice parameter of the material is expanded. These observations are discussed in terms of possible physical models and future experiments.